A high-quality recycled aggregate and its preparation method and application

Through high-temperature preheating, rolling, shape grinding and activation strengthening processes, combined with modified graphene oxide and modified lamellar sericite, the inherent defects of recycled aggregates and the space for improving the reinforcement effect of graphene oxide are solved, significantly Improved performance of recycled aggregates and ultra-high performance concrete.

CN119080416BActive Publication Date: 2025-01-24SICHUAN HIGHWAY PLANNING SURVEY DESIGN AND RESEARCH INSTITUTE LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411590038.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art fails to effectively solve the inherent defects of the recycled aggregate when making recycled aggregates, such as old mortar and fine gaps on the surface, and there is still room for improvement in the enhancement effect of graphene oxide.

Method used

Adopt high temperature pre -heating treatment, rolling treatment, styling repair and activation of reinforcement technology, through the self -made modified reinforcement liquid modified graphene and modified chromatographic silk Yunmu, which significantly improves the mechanical performance and decentralization of the recycled collection material Essence

Benefits of technology

It improves the mechanical properties and decentralization of the regenerative collection material, enhances the overall strength and freezing performance of ultra -high -performance concrete, and maintains excellent durability under the replacement rate of high regeneration collection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a high-quality recycled aggregate and its preparation method and application, which belongs to the technical field of recycled aggregate. The preparation of the high-quality recycled aggregate includes the following steps: S1, high-temperature preheating treatment, using microwave heating to heat the recycled aggregate to 450 degrees Celsius; S2, rolling treatment of recycled aggregate, using a jaw crusher to roll and crush the recycled aggregate after heat treatment, and sieving and grading to obtain recycled aggregate; S3, shaping and grinding recycled aggregate, placing the sieved and graded recycled aggregate in an eccentric grinding device for shaping and grinding; S4, activating the strengthening process, soaking the recycled aggregate in a self-made modified strengthening liquid, and waiting for the surface of the recycled aggregate to be fully coated with the liquid; taking it out and drying it, and then preparing high-quality recycled aggregate. The ultra-high performance concrete prepared by using the high-quality recycled aggregate of the present application can have relatively excellent freeze-thaw resistance and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of recycled aggregates, and specifically relates to high-quality recycled aggregates and a preparation method and application thereof. Background Art

[0002] With the progress of society, more and more concrete engineering structures are developing towards higher strength and better durability. Ultra-high performance concrete (UHPC); UHPC has broad application prospects in civil engineering due to its excellent mechanical properties and durability. However, the high cost of UHPC limits its widespread popularity in engineering; therefore, finding suitable materials to reduce the cost of UHPC preparation is a hot topic of research today.

[0003] With the continuous advancement of industrialization and urbanization, the construction industry has developed rapidly. At the same time, the emission of construction waste has also increased year by year.

[0004] If construction waste is directly dumped or piled into landfills, it is easy to cause land occupation, soil, air and water pollution, and even cause accidents. In addition, engineering construction consumes a large amount of raw materials, resulting in a shortage of natural aggregate resources in various places, which has a significant negative impact on the sustainability of engineering construction. Therefore, in order to solve the environmental pollution and raw material shortage problems caused by construction waste, it is of great significance to recycle construction waste into recycled aggregates and re-use them in concrete production to promote the sustainable development of the construction industry.

[0005] Prior art, such as the Chinese invention patent with application number 202310024376.5, discloses a graphene oxide reinforced recycled aggregate ultra-high performance concrete and a preparation method; it is characterized in that it comprises the following raw materials in parts by weight: 570-650 parts of cement, 150-180 parts of slag, 100-150 parts of metakaolin, 80-120 parts of limestone powder, 300-440 parts of regenerated sand, 50-80 parts of recycled micropowder, 700-1000 parts of quartz sand, 100-200 parts of quartz powder, 30-60 parts of polycarboxylate water reducer, 180-280 parts of water, and 0.5-0.8 parts of graphene oxide; it also includes steel fiber, and the volume of the steel fiber is 1.5-2.2% of the total volume of the concrete. The above-mentioned prior art adopts a spraying method to add graphene oxide, which can achieve a good dispersion effect, solve its agglomeration problem, make the graphene oxide evenly distributed on the surface of the aggregate, and achieve a significant reinforcement effect with a lower dosage.

[0006] The defect of the above technology is that it only performs basic crushing, cleaning and screening on the recycled aggregate, and the core is still to control the fineness modulus of the recycled aggregate; the problem is that some inherent defects of the waste concrete used to make the recycled aggregate, such as the presence of old mortar on its surface and possible tiny gaps, have not been solved; and the above-mentioned existing technology adds graphene oxide by spraying, which only increases the dispersion effect of graphene oxide from a physical level, and there is still huge room for improvement in the actual enhancement effect.

[0007] Therefore, there is an urgent need to introduce new process technologies to solve the above problems and seek more feasible solutions. Summary of the invention

[0008] In order to solve the defects existing in the above technical solutions, the purpose of the present invention is to provide a method for preparing high-quality recycled aggregate.

[0009] The preparation of the high-quality recycled aggregate comprises the following steps:

[0010] S1, high temperature preheating treatment, using microwave heating to heat the recycled aggregate to 450 degrees Celsius;

[0011] S2, rolling treatment of recycled aggregates, using a jaw crusher to roll and crush the recycled aggregates after heat treatment, and sieving and grading to obtain recycled aggregates;

[0012] S3, shaping and grinding the recycled aggregate, placing the sieved and graded recycled aggregate in an eccentric grinding device for shaping and grinding;

[0013] S4. Activate the strengthening process, immerse the recycled aggregate in the self-made modified strengthening liquid, and wait until the surface of the recycled aggregate is fully coated with the liquid; take it out and dry it, and high-quality recycled aggregate is prepared.

[0014] The strengthening treatment in step S4 uses a homemade modified strengthening liquid prepared by a method comprising the following steps: adding 25 parts by mass of polyvinyl alcohol to 130 parts by mass of deionized water, soaking at room temperature for 45 minutes to fully swell it, then heating it to 60 degrees Celsius, stirring it at a speed of 400 r / min for 2 hours until the polyvinyl alcohol is completely dissolved; then taking 0.8 parts by mass of modified graphene oxide and 0.5 parts by mass of modified lamellar sericite, blending the above mixed solution for 4 hours under the action of mechanical stirring and ultrasonic dispersion, and then standing it for defoaming to prepare a homemade modified strengthening liquid.

[0015] The strengthening treatment in step S4 comprises the following steps of: wrapping the recycled aggregate with a fishing net and placing it in a self-made modified strengthening liquid. The height of the self-made modified strengthening liquid needs to be higher than the recycled aggregate. The recycled aggregate is fully turned over every 30 minutes. After soaking for 4 hours, the modified recycled aggregate is taken out and the excess self-made modified strengthening liquid is filtered out.

[0016] Furthermore, in the strengthening treatment of step S4, the modified lamellar sericite in the homemade modified strengthening liquid is prepared by a method comprising the following steps: 2 ml of KH550 is added to a mixed solution of 100 ml of deionized water and 100 ml of anhydrous ethanol, and then glacial acetic acid is added dropwise to a pH of 5, and the mixed solution is placed in a 60 degree Celsius water bath for 1 hour to hydrolyze KH550, and then 25 g of lamellar mica powder is added, and the reaction is continued to be stirred at room temperature for 2 hours; finally, the reaction solution is centrifuged in a centrifuge, the upper layer solution is poured out, and anhydrous ethanol is added to shake and wash, the operation is repeated 2-3 times, and the remaining product is placed in an oven for drying, and the modified lamellar sericite is prepared.

[0017] Furthermore, in the strengthening treatment of step S4, the modified graphene oxide in the homemade modified strengthening solution is prepared by a method comprising the following steps: 50 mg of graphene oxide is placed in 95 g of N,N-dimethylformamide solution, ultrasonically treated for 1 hour, and stirred for 1 hour; then 0.39 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.26 g of N-hydroxysuccinimide are added; stirred for 2 hours under ice bath conditions; then 2.6 g of 1,5-diaminotetrazole is added to the mixed solution, and stirred at room temperature for 8 hours; then centrifuged, washed 3 times with ethanol and deionized water respectively, and then the product is dried to prepare the modified graphene oxide.

[0018] Furthermore, the drying process in step S4 is to dry the reinforced recycled aggregate in an environment of 20-25 degrees Celsius.

[0019] Furthermore, after filtering out excess homemade modified strengthening liquid, the aggregates after strengthening treatment need to be separated from the recycled aggregates that are bonded together to avoid aggregate bonding affecting performance.

[0020] The invention discloses an application of high-quality recycled aggregate, which can be used in ultra-high performance concrete.

[0021] The ultra-high performance concrete comprises the following components in parts by weight: 780-840 parts of cement, 80-100 parts of silica fume, 520-560 parts of high-quality recycled aggregate, 520-560 parts of natural fine aggregate, 145-160 parts of steel fiber, 165-195 parts of water, and 15-20 parts of water reducing agent;

[0022] Wherein, the application adopts high-quality recycled aggregate with 5-10mm continuous grading.

[0023] Furthermore, the ultra-high performance concrete is prepared by a method comprising the following steps: adding high-quality recycled aggregate, natural fine aggregate, steel fiber, cement, silica fume, and dry materials into a mixer in sequence and continuously stirring for 5 minutes, then stirring water and a water reducing agent into a homogeneous solution, adding the solution into the mixer, and continuing to stir for 5 minutes; thus, the ultra-high performance concrete is prepared.

[0024] The present invention has the beneficial effects:

[0025] 1. The 1,5-diaminotetrazole introduced in the present application can enhance the hydrophobicity of graphene oxide, and the modified graphene oxide prepared in the present application is applied to the reinforcement of recycled aggregates. The modified graphene oxide also has oxygen-containing groups, which can form hydrogen bonds with polyvinyl alcohol, reducing the number of free hydroxyl groups in the polyvinyl alcohol molecular chain; and the nanometer size and plate-like structure of the modified graphene oxide provide a large specific surface area; the graphene oxide layers overlap each other to form a large network structure, which can provide good material support, while maintaining good dispersibility and reducing the possibility of agglomeration;

[0026] 2. In the modified graphene oxide of the present application, due to the introduction of 1,5-diaminotetrazolyl functional groups, the interaction between the modified graphene oxide and other molecules is enhanced. During the water phase change process, the orderly arrangement of the ice lattice may be disrupted, thereby inhibiting the growth of ice crystals to a certain extent, so that the ultra-high performance concrete using high-quality recycled aggregates can have excellent freeze-thaw resistance;

[0027] 3. The present application introduces graphene oxide modified by 1,5-diaminotetrazolyl amidation into a homemade modified strengthening liquid; after the introduction and strengthening, the surface of the recycled aggregate becomes rougher, and the rough recycled aggregate can provide better mechanical interlocking force in the ultra-high performance concrete; and can also enhance the bonding performance between different materials in the ultra-high performance concrete, and improve the overall strength of the ultra-high performance concrete; and under the premise of a high replacement rate of recycled aggregate, it still has excellent durability, especially freeze-thaw resistance;

[0028] 4. The KH550 modified lamellar sericite introduced in the homemade modified strengthening liquid in this application has enhanced the compatibility of the organic phase and the inorganic phase. The modified lamellar sericite can be evenly dispersed in the homemade modified strengthening liquid, playing the role of a cross-linking point in the polymer chain, and can better cover the possible internal defects of the recycled aggregate, thereby improving the mechanical and barrier properties of the recycled aggregate. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment, and the illustrative embodiments of the present invention and its description are only used to explain the present invention, and are not used as limitation of the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper limit and lower limit of these smaller ranges can be independently included or excluded in the scope.

[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0033] The "parts" indicated in the following examples are all parts by weight.

[0034] Example 1

[0035] An ultra-high performance concrete using high-quality recycled aggregate, comprising the following components by weight: 780 parts of cement, 80 parts of silica fume, 520 parts of high-quality recycled aggregate, 520 parts of natural fine aggregate, 145 parts of steel fiber, 165 parts of water, and 15 parts of water reducing agent;

[0036] The cement is purchased from P.O42.5 ordinary Portland cement produced by Tongren Southwest Cement Co., Ltd.

[0037] The silica fume meets the requirements of GB / T 18736-2017 "Mineral admixtures for high-strength and high-performance concrete" for various physical performance indicators.

[0038] The natural fine aggregate is washed sand, purchased from Sichuan Haoying Chuangneng Mining Co., Ltd., with a bulk density of 1510kg / m 3 , apparent density is 2555kg / m 3 ;

[0039] The steel fiber is a straight copper-plated steel fiber with a length of 12 mm, a diameter of 0.2 mm, and a tensile strength of 2500 MPa;

[0040] Among them, the water reducer is a polycarboxylic acid water reducer, which is purchased from Shenyang Xingzhenghe Chemical Co., Ltd.

[0041] A method for preparing high-quality recycled aggregate, the preparation of the high-quality recycled aggregate comprising the following steps:

[0042] S1, high temperature preheating treatment, using microwave heating to heat the recycled aggregate to 450 degrees Celsius;

[0043] S2, rolling treatment of recycled aggregates, using a jaw crusher to roll and crush the recycled aggregates after heat treatment, and sieving and grading to obtain recycled aggregates;

[0044] S3, shaping and grinding the recycled aggregate, placing the sieved and graded recycled aggregate in an eccentric grinding device for shaping and grinding;

[0045] S4. Activate the strengthening process, immerse the recycled aggregate in the self-made modified strengthening liquid, and wait until the surface of the recycled aggregate is fully coated with the liquid; take it out and dry it, and high-quality recycled aggregate is prepared.

[0046] In specific implementation, the high temperature pretreatment in step S1 can achieve the purpose of weakening the old mortar layer on the surface;

[0047] In the specific implementation, in step S3, the recycled aggregate is shaped and ground. The recycled aggregate is ground by the high-speed rotating eccentric wheel, and the protruding edges and corners of the recycled aggregate and the old mortar on the surface are removed;

[0048] The immersion process of the activation and strengthening treatment in step S4 is as follows: wrap the recycled aggregate with a fishing net and put it into a homemade modified and strengthened liquid. The height of the homemade modified and strengthened liquid needs to be higher than the recycled aggregate. The recycled aggregate is fully turned over every 30 minutes. After soaking for 4 hours; the modified recycled aggregate is taken out, and the excess homemade modified and strengthened liquid is filtered out.

[0049] After filtering out the excess homemade modified strengthening liquid, the aggregates after strengthening treatment need to be separated from the recycled aggregates that are bonded together to avoid aggregate bonding affecting performance;

[0050] The drying process in step S4 is to dry the reinforced recycled aggregate in an environment of 20-25 degrees Celsius.

[0051] The self-made modified strengthening liquid is prepared by a method comprising the following steps: adding 25 parts by mass of polyvinyl alcohol to 130 parts by mass of deionized water, soaking at room temperature for 45 minutes to fully swell it, then heating it to 60 degrees Celsius, stirring it at a speed of 400 r / min for 2 hours, until the polyvinyl alcohol is completely dissolved; then taking 0.8 parts by mass of modified graphene oxide and 0.5 parts by mass of modified lamellar sericite, blending the above mixed solution for 4 hours under the action of mechanical stirring and ultrasonic dispersion, and then standing it for defoaming, so as to prepare the self-made modified strengthening liquid.

[0052] The preparation method of the modified lamellar sericite comprises the following steps: adding 2 ml of KH550 to a mixed solution of 100 ml of deionized water and 100 ml of anhydrous ethanol, then dropping glacial acetic acid to a pH of 5, placing the mixed solution in a water bath at 60 degrees Celsius for 1 hour to hydrolyze the KH550, then adding 25 g of lamellar mica powder, and continuing to stir and react at room temperature for 2 hours; finally centrifuging the reaction solution in a centrifuge, pouring out the upper layer solution, then adding anhydrous ethanol to shake and wash, repeating the operation 2-3 times, and then placing the remaining product in an oven for drying, thereby preparing the modified lamellar sericite.

[0053] The modified graphene oxide in the homemade modified strengthening solution is prepared by a method comprising the following steps: taking 50 mg of graphene oxide and placing it in 95 g of N,N-dimethylformamide solution, ultrasonically treating it for 1 hour, and stirring it for 1 hour; then adding 0.39 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.26 g of N-hydroxysuccinimide; stirring it for 2 hours under ice bath conditions; activating the carboxyl groups on the surface of the graphene oxide; then adding 2.6 g of 1,5-diaminotetrazole to the mixed solution, stirring it for 8 hours at room temperature; then centrifuging it, washing it with ethanol and deionized water for 3 times respectively, and then drying the product to prepare the modified graphene oxide.

[0054] The lamellar mica powder was purchased from Lingshou County Huayuan Mica Co., Ltd.

[0055] The polyvinyl alcohol was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0056] After the screening process in step S3, the apparent density of the obtained recycled aggregate was tested to be 2.32 g / cm 3 ; Water absorption is 6.9%; Crushing value is 21.5%.

[0057] After the strengthening treatment in step S4, the apparent density of the obtained high-quality recycled aggregate after strengthening is tested to be 2.72 g / cm 3 ; Water absorption is 2.8%; Crushing value is 9.3%.

[0058] An application of high-quality recycled aggregate in ultra-high performance concrete, wherein the high-quality recycled aggregate with continuous gradation of 5-10 mm is used;

[0059] In specific implementation, the high-quality recycled aggregate is 5-10mm continuously graded high-quality recycled aggregate;

[0060] In specific implementation, the recycled aggregates in Examples 1-5 and Comparative Examples 1-5 of the present application are all sourced from the same location and are prepared by crushing the recycled aggregates from the same batch.

[0061] Preparation of ultra-high performance concrete containing high-quality recycled aggregate: high-quality recycled aggregate, natural fine aggregate, steel fiber, cement, silica fume, and dry materials are added to a mixer in sequence and stirred for 5 minutes, and then water and a water reducing agent are stirred and mixed into a homogeneous solution, added to the mixer, and stirred for 5 minutes; thus, the ultra-high performance concrete is initially prepared;

[0062] Subsequently, the fully mixed ultra-high performance concrete is loaded into the mold twice. The first time, two-thirds of the mold is filled, and tamping is performed 20-30 times. The second time, the filling height is about 20mm higher than the mold, and tamping is continued for 20-30 times. After tamping, a flat vibrator is used to vibrate for about 30 seconds to form the ultra-high performance concrete. After the specimen is formed, the surface of the specimen is covered with plastic film and placed in a standard curing room for curing.

[0063] Example 2

[0064] An ultra-high performance concrete using high-quality recycled aggregate, comprising the following components by weight: 800 parts of cement, 85 parts of silica fume, 530 parts of high-quality recycled aggregate, 530 parts of natural fine aggregate, 151 parts of steel fiber, 170 parts of water, and 16 parts of water reducing agent;

[0065] Among them, in Example 2, except for the specific formula, the preparation method of high-quality recycled aggregate and the preparation method of ultra-high performance concrete are consistent with those in Example 1.

[0066] Example 3

[0067] An ultra-high performance concrete using high-quality recycled aggregate, comprising the following components by weight: 810 parts of cement, 90 parts of silica fume, 540 parts of high-quality recycled aggregate, 540 parts of natural fine aggregate, 155 parts of steel fiber, 180 parts of water, and 18 parts of water reducing agent;

[0068] Among them, in Example 3, except for the specific formula, the preparation method of high-quality recycled aggregate and the preparation method of ultra-high performance concrete are consistent with those in Example 1.

[0069] Example 4

[0070] An ultra-high performance concrete using high-quality recycled aggregate, comprising the following components by weight: 820 parts of cement, 95 parts of silica fume, 550 parts of high-quality recycled aggregate, 550 parts of natural fine aggregate, 158 parts of steel fiber, 190 parts of water, and 19 parts of water reducing agent;

[0071] Among them, in Example 4, except for the specific formula, the preparation method of high-quality recycled aggregate and the preparation method of ultra-high performance concrete are consistent with those in Example 1.

[0072] Example 5

[0073] An ultra-high performance concrete using high-quality recycled aggregate, comprising the following components by weight: 840 parts of cement, 100 parts of silica fume, 560 parts of high-quality recycled aggregate, 560 parts of natural fine aggregate, 160 parts of steel fiber, 195 parts of water, and 20 parts of water reducing agent;

[0074] Among them, in Example 5, except for the specific formula, the preparation method of high-quality recycled aggregate and the preparation method of ultra-high performance concrete are consistent with those in Example 1.

[0075] Comparative Example 1

[0076] An ultra-high performance concrete using recycled aggregates, comprising the following components by weight: 810 parts of cement, 90 parts of silica fume, 540 parts of recycled aggregates, 540 parts of natural fine aggregates, 155 parts of steel fibers, 180 parts of water, and 18 parts of a water reducing agent;

[0077] The cement is purchased from P.O42.5 ordinary Portland cement produced by Tongren Southwest Cement Co., Ltd.

[0078] The silica fume meets the requirements of GB / T 18736-2017 "Mineral admixtures for high-strength and high-performance concrete" for various physical performance indicators.

[0079] The natural fine aggregate is washed sand, purchased from Sichuan Haoying Chuangneng Mining Co., Ltd., with a bulk density of 1510kg / m 3 , apparent density is 2555kg / m 3 .

[0080] The steel fiber is a straight copper-plated steel fiber with a length of 12 mm, a diameter of 0.2 mm, and a tensile strength of 2500 MPa.

[0081] Among them, the water reducer is a polycarboxylic acid water reducer, which is purchased from Shenyang Xingzhenghe Chemical Co., Ltd.

[0082] In a specific implementation, the recycled aggregate is prepared by the following steps: S1, high-temperature preheating treatment, using microwave heating to heat the recycled aggregate to 450 degrees Celsius; S2, rolling treatment of the recycled aggregate, using a jaw crusher to roll and crush the recycled aggregate after heat treatment, and sieving and grading to obtain the recycled aggregate; S3, shaping and grinding the recycled aggregate, placing the sieved and graded recycled aggregate in an eccentric grinding device for shaping and grinding;

[0083] Among them, in comparative example 1, except that the activation and strengthening process in step S4 is not performed on the recycled aggregate, the preparation methods of the remaining ultra-high performance concrete and the test pieces are consistent with those in embodiment 3.

[0084] Comparative Example 2

[0085] An ultra-high performance concrete using recycled aggregates, comprising the following components by weight: 810 parts of cement, 90 parts of silica fume, 540 parts of recycled aggregates, 540 parts of natural fine aggregates, 155 parts of steel fibers, 180 parts of water, and 18 parts of a water reducing agent;

[0086] The cement is purchased from P.O42.5 ordinary Portland cement produced by Tongren Southwest Cement Co., Ltd.

[0087] The silica fume meets the requirements of GB / T 18736-2017 "Mineral admixtures for high-strength and high-performance concrete" for various physical performance indicators.

[0088] The natural fine aggregate is washed sand, purchased from Sichuan Haoying Chuangneng Mining Co., Ltd., with a bulk density of 1510kg / m 3 , apparent density is 2555kg / m 3 .

[0089] The steel fiber is a straight copper-plated steel fiber with a length of 12 mm, a diameter of 0.2 mm, and a tensile strength of 2500 MPa.

[0090] Among them, the water reducer is a polycarboxylic acid water reducer, which is purchased from Shenyang Xingzhenghe Chemical Co., Ltd.

[0091] In specific implementation, the recycled aggregate is prepared through steps S1-S4, with the difference being that step S4 adopts the following activation strengthening process.

[0092] The self-made modified strengthening liquid is prepared by a method comprising the following steps: adding 25 parts by mass of polyvinyl alcohol to 130 parts by mass of deionized water, soaking for 45 minutes at room temperature to fully swell it, then heating it to 60 degrees Celsius, stirring it at a speed of 400 r / min for 2 hours, until the polyvinyl alcohol is completely dissolved; then taking 0.8 parts by mass of graphene oxide and 0.5 parts by mass of modified lamellar sericite, blending the above mixed solution for 4 hours under the action of mechanical stirring and ultrasonic dispersion, and then standing it for defoaming, so as to prepare the self-made modified strengthening liquid.

[0093] The preparation method of the modified lamellar sericite in the self-made modified strengthening solution is the same as that in Example 3;

[0094] The graphene oxide in the self-made modified strengthening solution was purchased from Suzhou Carbonfeng Graphene Technology Co., Ltd.

[0095] Among them, in comparative example 2, except for the different strengthening treatment in step S4, the preparation methods of the rest of the ultra-high performance concrete and the test piece are the same as those in embodiment 3.

[0096] Comparative Example 3

[0097] An ultra-high performance concrete using recycled aggregates, comprising the following components by weight: 810 parts of cement, 90 parts of silica fume, 540 parts of recycled aggregates, 540 parts of natural fine aggregates, 155 parts of steel fibers, 180 parts of water, and 18 parts of a water reducing agent;

[0098] The cement is purchased from P.O42.5 ordinary Portland cement produced by Tongren Southwest Cement Co., Ltd.

[0099] The silica fume meets the requirements of GB / T 18736-2017 "Mineral admixtures for high-strength and high-performance concrete" for various physical performance indicators.

[0100] The natural fine aggregate is washed sand, purchased from Sichuan Haoying Chuangneng Mining Co., Ltd., with a bulk density of 1510kg / m 3 , apparent density is 2555kg / m 3 ;

[0101] The steel fiber is a straight copper-plated steel fiber with a length of 12 mm, a diameter of 0.2 mm, and a tensile strength of 2500 MPa.

[0102] Among them, the water reducer is a polycarboxylic acid water reducer, which is purchased from Shenyang Xingzhenghe Chemical Co., Ltd.

[0103] In specific implementation, the recycled aggregate is prepared through steps S1 to S4, except that step S4 adopts the following activation strengthening process:

[0104] The self-made modified strengthening liquid is prepared by a method comprising the following steps: adding 25 parts by mass of polyvinyl alcohol to 130 parts by mass of deionized water, soaking for 45 minutes at room temperature to fully swell it, then heating it to 60 degrees Celsius, stirring it at a speed of 400 r / min for 2 hours, until the polyvinyl alcohol is completely dissolved; then taking 0.5 parts by mass of modified lamellar sericite, blending the above mixed solution for 4 hours under the action of mechanical stirring and ultrasonic dispersion, and then standing it for defoaming, so as to prepare the self-made modified strengthening liquid.

[0105] The preparation method of the modified lamellar sericite in the self-made modified strengthening solution is the same as that in Example 3;

[0106] Among them, in comparative example 3, except for the activation and strengthening process in step S4, the preparation methods of the remaining ultra-high performance concrete and the test piece are the same as those in embodiment 3.

[0107] Comparative Example 4

[0108] An ultra-high performance concrete using recycled aggregates, comprising the following components by weight: 810 parts of cement, 90 parts of silica fume, 540 parts of recycled aggregates, 540 parts of natural fine aggregates, 155 parts of steel fibers, 180 parts of water, and 18 parts of a water reducing agent;

[0109] The cement is purchased from P.O42.5 ordinary Portland cement produced by Tongren Southwest Cement Co., Ltd.

[0110] Among them, the various physical performance indicators of the silica fume meet the requirements of GB / T 18736-2017 "Mineral admixtures for high-strength and high-performance concrete".

[0111] The natural fine aggregate is washed sand, purchased from Sichuan Haoying Chuangneng Mining Co., Ltd., with a bulk density of 1510kg / m 3 , apparent density is 2555kg / m 3 .

[0112] The steel fiber is a straight copper-plated steel fiber with a length of 12 mm, a diameter of 0.2 mm, and a tensile strength of 2500 MPa.

[0113] Among them, the water reducer is a polycarboxylic acid water reducer, which is purchased from Shenyang Xingzhenghe Chemical Co., Ltd.

[0114] In specific implementation, the recycled aggregate is prepared through steps S1 to S4, except that step S4 adopts the following activation strengthening process:

[0115] The homemade modified strengthening liquid is prepared by a method comprising the following steps: adding 25 parts by mass of polyvinyl alcohol to 130 parts by mass of deionized water, soaking at room temperature for 45 minutes to fully swell it, then heating it to 60 degrees Celsius, stirring it at a speed of 400 r / min for 2 hours until the polyvinyl alcohol is completely dissolved; then taking 0.8 parts by mass of modified graphene oxide, blending the above mixed solution for 4 hours under the action of mechanical stirring and ultrasonic dispersion, and then standing it for defoaming to prepare the homemade modified strengthening liquid.

[0116] The modified graphene oxide in the homemade modified strengthening solution is prepared by a method comprising the following steps: 50 mg of graphene oxide is placed in 95 g of N,N-dimethylformamide solution, ultrasonically treated for 1 hour, and stirred for 1 hour; then 0.39 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.26 g of N-hydroxysuccinimide are added; the mixture is stirred for 2 hours under ice bath conditions; then 2.6 g of 1,5-diaminotetrazole is added to the mixed solution, and the mixture is stirred for 8 hours at room temperature; then the mixture is centrifuged, washed with ethanol and deionized water for 3 times respectively, and then the product is dried to prepare the modified graphene oxide;

[0117] Among them, in comparative example 4, except for the activation and strengthening process in step S4, the preparation methods of the remaining ultra-high performance concrete and the test piece are the same as those in embodiment 3.

[0118] Comparative Example 5

[0119] An ultra-high performance concrete using recycled aggregates, comprising the following components by weight: 810 parts of cement, 90 parts of silica fume, 540 parts of recycled aggregates, 540 parts of natural fine aggregates, 155 parts of steel fibers, 180 parts of water, 18 parts of water reducing agent; 0.8 parts of modified graphene oxide, and 0.5 parts of modified lamellar sericite;

[0120] The cement is purchased from P.O42.5 ordinary Portland cement produced by Tongren Southwest Cement Co., Ltd.

[0121] The silica fume meets the requirements of GB / T 18736-2017 "Mineral admixtures for high-strength and high-performance concrete" for various physical performance indicators.

[0122] The natural fine aggregate is washed sand, purchased from Sichuan Haoying Chuangneng Mining Co., Ltd., with a bulk density of 1510kg / m3 and an apparent density of 2555kg / m3;

[0123] The steel fiber is a straight copper-plated steel fiber with a length of 12 mm, a diameter of 0.2 mm, and a tensile strength of 2500 MPa;

[0124] Wherein, the water reducer is a polycarboxylate water reducer, which is purchased from Shenyang Xingzhenghe Chemical Co., Ltd.;

[0125] The preparation and synthesis methods of the modified graphene oxide and modified lamellar sericite are the same as those in Example 3;

[0126] Among them, the recycled aggregate in comparative example 5 was not subjected to the activation and strengthening process of step S4.

[0127] Preparation of ultra-high performance concrete containing high-quality recycled aggregate: recycled aggregate, natural fine aggregate, steel fiber, cement, silica fume and dry materials are added into a mixer in sequence and stirred for 5 minutes, and then water, water reducing agent, polyvinyl alcohol, modified graphene oxide and modified lamellar sericite are stirred and mixed into a homogeneous solution, added into the mixer, and stirred for 5 minutes; thus, the ultra-high performance concrete is initially prepared;

[0128] Subsequently, the fully mixed ultra-high performance concrete is loaded into the mold twice. The first time, two-thirds of the mold is filled, and tamping is performed 20-30 times. The second time, the filling height is about 20mm higher than the mold, and tamping is continued for 20-30 times. After tamping, a flat vibrator is used to vibrate for about 30 seconds to form the ultra-high performance concrete. After the specimen is formed, the surface of the specimen is covered with plastic film and placed in a standard curing room for curing.

[0129] Among them, in Comparative Example 5, the recycled aggregate was not treated by the activation and strengthening process, but a homemade modified strengthening liquid was added during the preparation of ultra-high performance concrete.

[0130] Performance test of ultra-high performance concrete:

[0131] The test blocks prepared in Examples 1-5 and Comparative Examples 1-5, all indicators are the data measured after curing in a standard curing room for 28 days;

[0132] Among them, the test of compressive strength and flexural strength of ultra-high performance concrete refers to GB / T17671-2021 "Test Method for Strength of Cement Mortar", and a microcomputer-controlled fully automatic pressure testing machine is used to complete the test.

[0133] Among them, the freeze-thaw performance test of ultra-high performance concrete is carried out with reference to GB / T 50082-2009 "Test method for long-term durability of ordinary concrete";

[0134] Test the relative dynamic elastic modulus, compressive strength loss rate, and mass loss rate after freeze-thaw cycles under 100 freeze-thaw cycles;

[0135] The test results of Examples 1-5 and Comparative Examples 1-5 are shown in Table 1;

[0136] Table 1

[0137]

[0138] Analysis of the test results of high-quality recycled aggregate application and ultra-high performance concrete performance: Comparative Example 1 and Comparative Example 5 did not perform any activation and strengthening process operations on the recycled aggregate. The 28-day flexural strength, 28-day compressive strength, relative dynamic elastic modulus after freeze-thaw, freeze-thaw compressive strength loss, and freeze-thaw mass loss of both are relatively poor and cannot reach the level that can be put into practical application. The fundamental reason is that: old mortar is commonly found on the surface of the current recycled aggregate, and after two steps of crushing, the recycled aggregate has tiny cracks and pores on its surface when it is not subjected to external loads; and the preparation process S3 of this application, during the modeling and grinding process, is prone to cause the recycled aggregate to continue to produce tiny cracks, thereby causing secondary losses of the recycled aggregate; it also increases the crack expansion on the surface of the recycled aggregate.

[0139] Although Comparative Example 5 added components of the homemade modified strengthening liquid such as modified graphene oxide and modified lamellar sericite during the preparation of ultra-high performance concrete containing recycled aggregate; and although there was a certain performance improvement compared with other comparative examples; however, they were added during the preparation of concrete, and the activation strengthening process of Examples 1-5 of the present application was not adopted; therefore, Comparative Example 5 still had a large performance gap with Examples 1-5 of the present application.

[0140] The homemade modified strengthening liquid in Comparative Example 2 uses graphene without any modification, and its 28-day compressive strength is 25% weaker than that of Example 3; although in terms of compressive strength, the gap between Comparative Example 2 and Examples 1-5 of the present application is small; this may be related to the mix ratio of the high-performance concrete of the present application. The data in Table 1 show that in Comparative Example 2, in the activation and strengthening process of S4, the unmodified graphene oxide in the homemade modified strengthening liquid, although all performances are better than those of Comparative Example 1 and Comparative Example 5, but after 100 freeze-thaw cycles, its relative dynamic elastic modulus, compressive strength loss rate, and mass loss rate are significantly different from those of Examples 1-5. The possible reasons are: in Examples 1-5, by introducing 1,5-diaminotetrazolyl amidation-modified graphene oxide into the homemade modified strengthening liquid; after the introduction and strengthening, the surface of the recycled aggregate is made rougher, and the rough recycled aggregate can provide better mechanical interlocking force in the ultra-high performance concrete; and it can also enhance the bonding performance between different materials in the ultra-high performance concrete, and improve the overall strength of the ultra-high performance concrete; so that the 28-day compressive strength is significantly better than that of Comparative Example 2.

[0141] In addition, in the modified graphene oxide of Examples 1-5, due to the introduction of 1,5-diaminotetrazolyl functional groups, the interaction between the modified graphene oxide and other molecules is enhanced. During the water phase change process, the orderly arrangement of the ice lattice may be disrupted, thereby inhibiting the growth of ice crystals to a certain extent, so that the ultra-high performance concrete using high-quality recycled aggregates can have excellent freeze-thaw resistance; that is, it shows excellent compressive strength loss rate and mass loss rate after 100 freeze-thaw cycles.

[0142] In Comparative Example 3, there is only modified lamellar sericite in the homemade modified and strengthened liquid; while in Comparative Example 4, no modified lamellar sericite is added to the homemade modified and strengthened liquid; among Comparative Examples 1-5, Comparative Example 4 has the best mechanical properties and freeze-thaw resistance, but there is a certain gap with Examples 1-5. The possible reasons are: the KH550 modified lamellar sericite introduced into the homemade modified and strengthened liquid, the modified lamellar sericite enhances the compatibility of the organic phase and the inorganic phase; the modified lamellar sericite can be evenly dispersed in the homemade modified and strengthened liquid, plays the role of a cross-linking point in the polymer chain, can better cover the possible internal defects of the recycled aggregate, and improve the mechanical and barrier properties of the recycled aggregate.

[0143] The modified graphene oxide also has oxygen-containing groups. When used in the reinforcement of recycled aggregates, the modified graphene oxide can form hydrogen bonds with polyvinyl alcohol, reducing the number of free hydroxyl groups in the polyvinyl alcohol molecular chain; and the nanosize and plate-like structure of the modified graphene oxide provide a large specific surface area; the graphene oxide layers overlap with each other to form a large network structure, which can provide good material support while maintaining good dispersion and reducing the possibility of agglomeration.

[0144] Especially in colder areas, freezing can easily cause expansion, changes in volume and mass, and greatly affect its performance, causing concrete cracks, thereby weakening the performance of high-quality recycled aggregate ultra-high performance concrete.

[0145] After hundreds of freeze-thaw tests, Examples 1-5 of the present application can still basically maintain the original performance without being damaged, which can fully verify the durability of the ultra-high performance concrete using the high-quality recycled aggregate of the present application.

[0146] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing high-quality recycled aggregate, characterized in that: The preparation of the high-quality recycled aggregate comprises the following steps: S1, high temperature preheating treatment, using microwave heating to heat the recycled aggregate to 450 degrees Celsius; S2, rolling treatment of recycled aggregates, using a jaw crusher to roll and crush the recycled aggregates after heat treatment, and sieving and grading to obtain recycled aggregates; S3, shaping and grinding the recycled aggregate, placing the sieved and graded recycled aggregate in an eccentric grinding device for shaping and grinding; S4, activate the strengthening process, soak the recycled aggregate in the self-made modified strengthening liquid, wait until the surface of the recycled aggregate is fully coated with the liquid; take it out and dry it, and then prepare high-quality recycled aggregate; In the step S4, the homemade modified strengthening liquid used for strengthening treatment is prepared by a method comprising the following steps: adding polyvinyl alcohol to deionized water, soaking it at room temperature for 45 minutes to fully swell it, then heating it to 60 degrees Celsius, stirring it at a speed of 400 r / min for 2 hours, until the polyvinyl alcohol is completely dissolved; then taking modified graphene oxide and modified lamellar sericite, blending them for 4 hours under the action of mechanical stirring and ultrasonic dispersion, and then standing them for defoaming, so as to prepare the homemade modified strengthening liquid; The modified lamellar sericite in the homemade modified strengthening solution used in step S4 is prepared by a method comprising the following steps: adding KH550 to a mixed solution of deionized water and anhydrous ethanol, then dropping glacial acetic acid until the pH is 5, placing the mixed solution in a water bath at 60 degrees Celsius for 1 hour to hydrolyze KH550, then adding lamellar mica powder, and continuing to stir and react at room temperature for 2 hours; finally, centrifuging the reaction solution in a centrifuge, pouring out the upper layer solution, then adding anhydrous ethanol to shake and wash, repeating the operation 2-3 times, and then placing the remaining product in an oven for drying, thereby preparing the modified lamellar sericite; The modified graphene oxide in the homemade modified strengthening solution used in step S4 is prepared by a method comprising the following steps: placing graphene oxide in an N,N-dimethylformamide solution, ultrasonically treating for 1 hour, and stirring for 1 hour; then adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide; stirring for 2 hours under ice bath conditions; then adding 1,5-diaminotetrazole to the mixed solution, stirring at room temperature for 8 hours; then centrifuging, washing with ethanol and deionized water for 3 times respectively, and then drying the product to prepare the modified graphene oxide.

2. The method for preparing high-quality recycled aggregate according to claim 1, characterized in that: In step S4, the soaking process of the strengthening treatment is: wrap the recycled aggregate with a fishing net and put it into a self-made modified strengthening liquid. The height of the self-made modified strengthening liquid needs to be higher than the recycled aggregate. The recycled aggregate is fully turned over every 30 minutes. After soaking for 4 hours; the modified recycled aggregate is taken out, and the excess self-made modified strengthening liquid is filtered out.

3. The method for preparing high-quality recycled aggregate according to claim 1, characterized in that: In the step S4, during the drying process, the reinforced recycled aggregate is dried in an environment of 20-25 degrees Celsius.

4. The method for preparing high-quality recycled aggregate according to claim 1, characterized in that: The high-quality recycled aggregate needs to be separated from the recycled aggregates that are bonded together after filtering out excess homemade modified strengthening liquid.

5. The use of high-quality recycled aggregate prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The high-quality recycled aggregate is used for ultra-high performance concrete.

6. The use of high-quality recycled aggregate according to claim 5, characterized in that: The ultra-high performance concrete comprises the following components in parts by weight: 780-840 parts of cement, 80-100 parts of silica fume, 520-560 parts of high-quality recycled aggregate, 520-560 parts of natural fine aggregate, 145-160 parts of steel fiber, 165-195 parts of water, and 15-20 parts of water reducing agent; Wherein, the application adopts high-quality recycled aggregate with 5-10mm continuous grading.

7. The use of high-quality recycled aggregate according to claim 5, characterized in that: The ultra-high performance concrete is prepared by a method comprising the following steps: adding high-quality recycled aggregate, natural fine aggregate, steel fiber, cement, silica fume and dry materials into a mixer in sequence and continuously stirring for 5 minutes, then stirring water and a water reducing agent to form a homogeneous solution, adding the solution into the mixer, and continuing to stir for 5 minutes; thus, the ultra-high performance concrete is prepared.

Citation Information

Patent Citations

  • Graphene oxide reinforced recycled aggregate ultra-high performance concrete and preparation method thereof

    CN116217162A

  • Preparation method of freeze-thaw resistant recycled concrete

    CN115321914A